How do you (demonstrate) care in an institution that does not define 'care'?. (3rd July 2021) - Baice, Tim; Fonua, Sonia M.; Levy, Ben; Allen, Jean M.; Wright, Tepora
ABSTRACT: Against a global pandemic, student care is in sharp focus for higher education institutions (HEIs) as students and institutions learn to navigate this context. Despite this, tensions exist between approaches to care and its value in HEIs. The neoliberalism underpinning HEIs results in the practice of care often being minimised. This is problematic as care is significant for its impact on student experiences. To demonstrate care, beyond simply service delivery, it is critical to develop a relational approach, especially for students who are already part of equity groups. The care demonstrated for these students has become more critical during the COVID-19 pandemic, and this paper focuses on Pacific and International students. We discuss the challenges negotiating how to demonstrate care when care is undefined and undervalued. Adding to the complexity, gaps continue in practice despite broad statements made by HEIs regarding cultural inclusivity. We describe our experiences as care practitioners before and during the pandemic in HEIs in Aotearoa New Zealand and the United States (U.S.), what informs our practice, and how we negotiate barriers. Employing talanoa and thematic analysis, we identified commonalities in our experiences. There was a clear gap in institutional definitions of care and understanding approaches by care practitioners. For us, a strong relational approach to care is paramount to effective practice, and even more so during a pandemic; however, this is contrasted by the many tensions described. Finally, we recognise the opportunities that arose from the pandemic for innovation focusing on student equity, which must continue post-pandemic.